Analisis Kemampuan Berpikir Kreatif Matematis Siswa Kelas XI pada Materi Lingkaran - Sha'adah, Innarotus; Rasiman, Rasiman; Setiawan, Agus (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to describe students' mathematical creative thinking abilities on the topic of circles. The research method used is qualitative descriptive. The research instruments consist of essay tests covering indicators of creative thinking, interviews, and documentation. The subjects selected for this study were students of class XI-10 at SMA Negeri 2 Semarang, from whom 2 students representing each category of creative thinking ability were selected for analysis of their work. The basis for selecting these subjects is through the interpretation of scores on the creative thinking ability test obtained in the form of percentages according to their qualifications. Data were analyzed qualitatively through data reduction, data presentation, and drawing conclusions. Data validity was ensured using method triangulation. The research results indicate that among the class XI-10 students in this study, there are 2 students with creative thinking abilities in the creative category fulfilling 3 out of the total 4 indicators. There are 2 students with creative thinking abilities in the fairly creative category who fulfill 2 indicators. Meanwhile, among students with creative thinking abilities in the less creative category, there is 1 student who only fulfills 1 indicator and 1 student who does not fulfill all indicators.